Back to Bataan - Dmytryk, Edward (Turner Entertainment Co., 2007)
1942, The Philippines. Enemy forces take control of the island nation. But as one type of war ends, another begins. Col. Joseph madden and others like him organize uncaptured Amefrican troops and Philippine fighters into effective guerrilla-warfare operatives.